Nursing Informatics Research Trends: Findings from an International Survey - Peltonen Laura-Maria; Nibber Raji; Block Lorraine; Ronquillo Charlene; Lozada Perezmitre Erika; Lewis Adrienne; Alhuwail Dari; Ali Samira; Georgsson Mattias; Jeon Eunjoo; Tayaben Jude L; Lee Ying-Li; et al. (Netherlands, 2022)
This follow-up survey on trends in Nursing Informatics (NI) was conducted by the International Medical Informatics Association (IMIA) Student and Emerging Professionals (SEP) group as a cross-sectional study in 2019. There were 455 responses from 24 countries. Based on the findings NI research is evolving rapidly. Current ten most common trends include: clinical quality measures, clinical decision support, big data, artificial intelligence, care coordination, education and competencies, patient safety, mobile health, description of nursing practices and evaluation of patient outcomes. The findings help support the efforts to efficiently use resources in the promotion of health care activities, to support the development of informatics education and to grow NI as a profession.
Nurses and Midwives in the Digital Age